Daoist Criticisms of Confucian Sacrificial Rites - Moeller, Hans-Georg (Sophia, 2012)
Various passages in the Laozi and the Zhuangzi, the two most important texts of “philosophical Daoism,” critically mock Confucian sacrificial rites. Perhaps the best known of these criticisms refers to a practice involving straw dogs (Laozi 5, Zhuangzi 14). This article will attempt to expose the philosophical dimensions of these passages that show, in my reading, how Daoist philosophy looks at such sacrificial rituals as a sort of evidence of the Confucian misconceptions of time, of death and life, and of cosmic and social order.